Effect of spray tips and mix deposition on common water hyacinth growing with varied population arrangements of salvinia and water lettuce - De Marchi, Sidnei Roberto (2009)
Volume around 200 L/ha. The TXVK-8 tip provided greater spray mix deposition when compared to the DG 11002VS dp, regardless of the plant propordons. For both spray tips, higher propordons of eared watermoss and the triple association among the plants provided the highest spray mix deposidon on water hyacinth plants. The increase of spray mix deposidon is likely related to the increase of eared watermoss or water lettuce as well as the decrease of water hyacinth plants in the association and consequent decreases of self covering among water hyacinth leaves. Lake managers should consider that improved herbicide uptake is possible through the choice of nozzle as well as applying herbicides to hyacinth before it forms dense monocultures or dense mixtures with other free-floating plants.